The strategy dilemma: Why big business moves seldom pan out as planned - Niceto S. Poblador (University of the Philippines, School of Economics (UPSE), 2011)
This article looks at the complex dynamics that underlie organizational change and attempts to explain why, under present uncertain environmental conditions, it is not possible to determine in advance the results of strategic moves made by business and other types of organizations. It explores the practical applications of systems simulation and experimental methods to the management of change in today's highly interconnected and knowledge-driven world.
Keywords: 330; Organisatorischer Wandel; Strategisches Management; Simulation